Peran Mahasiswa Dalam Peningkatan Kualitas Literasi Sebagai Wujud Pengabdian Kepada Masyarakat Di Desa Tajinan Kabupaten Malang - Citra Ayu Winie Febrianti; Irfan Arya Widya; Hayyu Imtiyaz; Sarah Maryam Hafidza; Rahmah Alia Handini; Tabitha Hosianna Hutagaol; Najma Athala Kayyisa; Nayla Azzahra Hanggita; Cut Tera Cantika; Muhammad Annas Satria; Dian Novita Dewi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
This community service program was conducted to improve children's literacy skills in Tajinan Village, Malang Regency through various engaging educational activities. The main problems identified were low reading interest among children and lack of parental understanding about the importance of literacy for their children's future. The method used was a participatory approach where students collaborated with the community, youth organizations, and teachers during the period of July 9 to August 7, 2025. The main programs implemented included awareness of the prominent of literacy, a literacy competition entitled